Treatment strategies of ruptured intracranial aneurysms associated with moyamoya disease. (4th March 2021) - Zhao, Xu; Wang, Xiaofei; Wang, Minqing; Meng, Qinghu; Wang, Chengwei
Abstract: Objective: The purpose of this study was to present our experience in the management of ruptured intracranial aneurysms associated with moyamoya disease (MMD), and to discuss their treatment strategies and the timing of revascularization surgery. Patients and methods: Thirteen patients who had ruptured intracranial aneurysms associated with MMD were enrolled in this study. Different treatment strategies were adopted based on the location of the aneurysms. Their clinical and radiologic features, treatment selection and outcomes were retrospectively reviewed. Results: Among the five patients with major artery aneurysms in anterior circulation, three were embolized and two clipped. Among the five patients with major artery aneurysms in posterior circulation, three were treated by endovascular coiling. Among the three peripheral aneurysms, one was treated by endovascular embolization, one by aneurysmectomy, and the other one by revascularization alone. For the patients whose aneurysms were treated by endovascular embolization or surgery, a staged revascularization was performed on day 28 to day 87 after the first operation. For the two patients with aneurysms untreated directly, the timing of revascularization was 20 days and 54 days after hemorrhage, respectively. During the follow-up recurrent intracranial hemorrhage occurred in a patient, but not caused by the previous aneurysm. No other patients suffered recurrent intracranial hemorrhage or ischemic stroke. Complete occlusion was achieved in all the 11 aneurysms that had been clipped or embolized. Of the remaining three aneurysms that had not been directly treated, one disappeared spontaneously, whereas the other two remained stable. The direct and indirect bypasses were confirmed patent in the 11 patients who had undergone revascularization. Conclusion: Our current treatment strategies and timing of revascularization may provide a benefit for the patients with MMD accompanied by ruptured intracranial aneurysms.